2020
DOI: 10.7717/peerj.8982
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of sequence variants in genes of Wnt signaling and focal adhesion pathways in human corneas further explains their involvement in keratoconus

Abstract: Background Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in loss of visual acuity. The etiology of KTCN remains unclear. The purpose of this study was to assess the potential involvement of new genetic variants in KTCN etiology based on both the genomic and transcriptomic findings recognized in the same corneal tissues. Methods Corneal tissues derived from five unrelated Polish individuals with KTCN were examined using exome sequencing (ES), followed by enrichment analyses. For com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
9
13
0
Order By: Relevance
“…Also, it indicates that abnormal expression of particular elements of the TGF-β, Hippo, and Wnt pathways might alter signaling crosstalk between these cascades in KTCN. Of note, our recent ES findings showed the accumulation of variants in several genes from Wnt signaling and/or focal adhesion pathways, deregulated in KTCN, further supporting possible involvement of these genes in disease etiology (Karolak et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Also, it indicates that abnormal expression of particular elements of the TGF-β, Hippo, and Wnt pathways might alter signaling crosstalk between these cascades in KTCN. Of note, our recent ES findings showed the accumulation of variants in several genes from Wnt signaling and/or focal adhesion pathways, deregulated in KTCN, further supporting possible involvement of these genes in disease etiology (Karolak et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…The most significant downregulation was observed among genes belonging to the TGF-β, Hippo, and Wnt signaling and collagen synthesis and maturation networks that are responsible for proper corneal organization and regulation of corneal ECM remodeling (Kabza et al, 2017). Abnormalities within genes involved in ECM have also been reported in subsequent RNA-and DNA-based studies (Khaled et al, 2018;You et al, 2018;Sharif et al, 2019;Karolak et al, 2020). Thus, disruptions within these molecular cascades could be potentially responsible for corneal changes underlying the development of KTCN.…”
Section: Introductionmentioning
confidence: 97%
“… 45 P4HB encodes an enzyme involved in the hydroxylation of prolyl residues in preprocollagen, which serves to stabilize the collagen triple helices. 46 Our findings suggest that some nuclear genes, due to their involvement in ECM organization and collagen synthesis or focal adhesion pathways, which were previously indicated as being deregulated in Polish KTCN corneas based on DNA and RNA studies, 20 , 37 , 47 play a role in disease pathogenesis. However, the direct function of these genes and their impact on mitochondrial function or oxidative stress in KTCN remain to be elucidated.…”
Section: Discussionsupporting
confidence: 52%
“…More than half of the genes were reported in one type of study or in single studies. A few genes, encoded chains of collagens ( COL5A1, COL4A3 , and COL4A4 ) ( 57 , 59 , 61 , 67 , 72 , 76 , 78 , 84 , 87 , 88 , 90 ), collagen cross-linking enzyme ( LOX ) ( 18 , 30 , 90 ), factor for the synthesis or organization of collagen fibers ( ZNF469 ) ( 27 , 32 , 34 , 46 , 47 , 62 , 65 ), and others ( MIR184 and VSX1 ) ( 6 , 7 , 16 , 19 , 24 , 40 , 56 , 82 , 85 ) were identified in different types of studies, such as pathogenic mutation analysis, polymorphism association analysis, and family-based linkage analysis. However, the occurrence rate of these gene mutations in the population was relatively low, and in many populations, it could not even be verified ( 25 , 195 – 202 ), which suggested that KC is genetically heterogeneous.…”
Section: Discussionmentioning
confidence: 99%